2015
DOI: 10.1074/jbc.m114.634840
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfers in a Channelrhodopsin-1 Studied by Fourier Transform Infrared (FTIR) Difference Spectroscopy and Site-directed Mutagenesis

Abstract: Background: Channelrhodopsin-1 is a red-shifted light-gated cation channel. Results: Proton transfers and H-bonding changes involving the Schiff base counterion residues Asp-169 and Glu-299 were detected. Conclusion: A two-step proton transfer relay mechanism consistent with our results and earlier photoinduced channel current and pH titration measurements is proposed. Significance: Understanding the mechanism of channelrhodopsin can lead to improved optogenetic control of neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
(83 reference statements)
4
23
0
Order By: Relevance
“…Resonance Raman spectroscopy data are not consistent with this residue acting as a Schiff base counterion at neutral pH, but it cannot be excluded that Glu68 deprotonates early in the photocycle and accepts a proton from the Schiff base during formation of the M intermediate (149). A similar “two-step” process has been shown by resonance Raman and FTIR-difference spectroscopy for the Asp85 homolog in the cation channelrhodopsin Ca ChR1 (98). The role of Glu68 as a proton acceptor in Gt ACR1 is supported by the Glu68-dependence of an outward proton transfer current evident in a mutant in which the second photoactive site carboxylate, Asp234, is neurtralized (136).…”
Section: The Known Molecular Functions Of Microbial Rhodopsinssupporting
confidence: 59%
See 1 more Smart Citation
“…Resonance Raman spectroscopy data are not consistent with this residue acting as a Schiff base counterion at neutral pH, but it cannot be excluded that Glu68 deprotonates early in the photocycle and accepts a proton from the Schiff base during formation of the M intermediate (149). A similar “two-step” process has been shown by resonance Raman and FTIR-difference spectroscopy for the Asp85 homolog in the cation channelrhodopsin Ca ChR1 (98). The role of Glu68 as a proton acceptor in Gt ACR1 is supported by the Glu68-dependence of an outward proton transfer current evident in a mutant in which the second photoactive site carboxylate, Asp234, is neurtralized (136).…”
Section: The Known Molecular Functions Of Microbial Rhodopsinssupporting
confidence: 59%
“…A novel two-step proton relay mechanism that transfers a proton from the Asp85 homolog to the Asp212 homolog during the primary phototransition and from the Schiff base to the Asp85 homolog during M formation has been proposed for Ca ChR1 based on FTIR (Fourier Transform Infrared) difference spectroscopy (98). Intramolecular proton transfer currents are not detected by patch clamp recording from Cr ChR2 and other high-efficiency CCRs, although an outward intramolecular proton transfer is observed in weaker CCRs such as Ca ChR1 (96).…”
Section: The Known Molecular Functions Of Microbial Rhodopsinsmentioning
confidence: 99%
“…Steady-state Fourier-transform infrared (FTIR) spectroscopic experiments helped to identify similar conformational changes and (de-) protonation events in ChR2 (6,19,20) and ChR1-ChR2 chimeras (21,22) from C. reinhardtii. Different conformational and protonation changes have been deduced from steady-state FTIR experiments on ChR1 from Chlamydomonas augustae (23)(24)(25)(26). For ChR2 we have further shown by time-resolved FTIR spectroscopy that D253 acts as primary acceptor of the Schiff-base proton and D156 as primary donor (7).…”
Section: Introductionmentioning
confidence: 98%
“…Comparison with static FTIR difference spectrum recorded at −23°C revealed that the backbone structural changes at lower temperature are partially blocked. This method has been used routinely in our laboratory to study a wide-range of microbial rhodopsins including sensory rhodopsins [31,32], proteorhodopsins [33,129] and channelrhodopsins [175].…”
Section: Kj Rothschild / the Early Development And Application Of Fmentioning
confidence: 99%
“…These studies were all conducted in collaboration with John Spudich, a leader in the microbial rhodopsin field at the University of Texas Health Science Center at Houston. They included FTIR difference studies along with RRS on halorhodopsin (HR) [197], sensory rhodopsins (SRI, SRII) from archaebacterial [29,31,34,38,184], fungal neurospora rhodopsin (NO) [30], anabaena sensory rhodopsin from cyanobacteria (ASR) [32], green and blue proteorhodopsin proton pumps from marine bacteria (PRs) [4,5,24,28,33,129,130]; archaerhodopsins-3 (AR3), a BR-like protein [56,216] and most recently channelrhodopsins (ChRs) from algae [173,174,176,250]. These proteins span a range of functions which are representative of diverse biomembranes process and include active anion transport (HRs), signal transduction (SRI, SRII and ASR), and light-gated ion channels (ChRs).…”
Section: Beyond Bacteriorhodopsinmentioning
confidence: 99%